New partnership for development and competitiveness: a Caribbean Basin proposal - Salazar-Xirinachs, Jose M. (CCS GeorgetownGY, 1993)
Recommends for the Central American and Caribbean countries a High Quality International Insertion Strategy which is based on four pillars viz. freer trade and more open local and foreign markets; improvement of the investment climate; regional integration; and active efforts to develop long term competitiveness.